Exploring high mortality rates among people with multiple and complex needs: a qualitative study using peer research methods. Issue 6 (3rd June 2021) - Perry, Rachel; Adams, Emma A.; Harland, Jill; Broadbridge, Angela; Giles, Emma L.; McGeechan, Grant J.; O'Donnell, Amy; Ramsay, Sheena E.
Abstract : Objective: To explore the perceived reasons underlying high mortality rates among people with multiple and complex needs. Design: Qualitative study using peer research. Setting: North East of England. Participants: Three focus group discussions were held involving (1) people with lived experience of multiple and complex needs (n=5); (2) front-line staff from health, social care and voluntary organisations that support multiple and complex needs groups (n=7); and (3) managers and commissioners of these organisations (n=9). Results: Findings from this study provide valuable perspectives of people with multiple complex needs and those that provide them with support on what may be perceived factors underlying premature mortality. Mental ill health and substance misuse (often co-occurring dual diagnosis) were perceived as influencing premature mortality among multiple and complex needs groups. Perceptions of opportunities to identify people at risk included critical life events (eg, bereavement, relationship breakdown) and transitions (eg, release from prison, completion of drug treatment). Early prevention, particularly supporting young people experiencing adverse childhood experiences, was also highlighted as a priority. Conclusion: High mortality in multiple and complex needs groups may be reduced by addressing dual diagnosis, providing more support at critical life events and investing in early prevention efforts. Future interventions could take into consideration the intricate nature of multiple and complex needs and improve service access and navigation.